2009
DOI: 10.3200/jexe.77.4.409-438
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Transactions Among Motives, Emotional Regulation Related to Testing, and Test Emotions

Abstract: The authors examined the relationships among achievement motives, emotional regulation, and emotions. They collected data from 425 college undergraduates (110 men, 315 women) and used several scales, including the Achievement Motives Scales ). Findings suggest that approach-avoidance motives were related to different academic emotions (i.e., pleasant and unpleasant) in the expected directions. Approach-avoidance variables, cognitive-appraisal processes, and during-testing processes explained significant amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
(60 reference statements)
2
8
1
5
Order By: Relevance
“…The metacognitive learning strategies were associated with the emotional regulation total scale and with the age group. These data are relevant to the extent that students, according to the research, when becoming more strategic in their learning and when coping better with their emotions, may also present better academic performance (DeCuir-Gunby et al, 2009;Kesici & Erdogan, 2009;Pekrun et al, 2002Pekrun et al, , 2011Raftery & Bizer, 2009). It should also be mentioned that one of the limitations of this study is related to the fact that it employed only the report of the use of learning strategies and emotional regulation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The metacognitive learning strategies were associated with the emotional regulation total scale and with the age group. These data are relevant to the extent that students, according to the research, when becoming more strategic in their learning and when coping better with their emotions, may also present better academic performance (DeCuir-Gunby et al, 2009;Kesici & Erdogan, 2009;Pekrun et al, 2002Pekrun et al, , 2011Raftery & Bizer, 2009). It should also be mentioned that one of the limitations of this study is related to the fact that it employed only the report of the use of learning strategies and emotional regulation.…”
Section: Discussionmentioning
confidence: 97%
“…Pekrun et al (2002Pekrun et al ( , 2011 showed that various emotions are related to the essential components of the self-regulation of learning, such as interest, motivation, and learning strategies, among others. DeCuir-Gunby et al (2009) found that low academic productivity of university students seems to be related to the use of emotional regulation strategies that do not favor adaption, for example, not facing up to the situation, rumination or isolation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effectively regulating emotions and expecting success fosters positive outcomes including psychological health, whereas feelings of helplessness are considered psychological risk factors (e.g., Folkman et al 1986). For example, in an academic context, mastery-oriented responses predicted greater self-efficacy and optimistic expectations, whereas helpless responses predicted greater levels of test anxiety and self-blame (DeCuir-Gunby et al 2009). Furthermore, self-efficacy predicts achievement across an array of domains including academics; self-efficacy is a powerful predictor of persistence, emotional reactions, and future academic achievement (e.g., Schunk 1989;Zimmerman 2000).…”
Section: Introductionmentioning
confidence: 97%